Ultrasensitive electrochemical detection of methyl parathion pesticide based on cationic water-soluble pillar[5]arene and reduced graphene nanocomposite. Issue 1 (2nd January 2019) - Tan, Xiaoping; Liu, Yan; Zhang, Tingying; Luo, Shasha; Liu, Xi; Tian, Hexiang; Yang, Yang; Chen, Chunlian
Abstract : A promising electrochemical sensing platform for the detection of methyl parathion based on cationic water-soluble pillar[5]arene reduced graphene nanocomposite. Abstract : We report a rapid, sensitive and selective electrochemical sensor based on pillar[5]arene (CP5) reduced graphene (rGO) nanohybrid-modified glassy carbon electrode CP5-rGO/GCE for the trace detection of methyl parathion (MP) by differential pulse voltammetry (DPV) for the first time. Compared to beta-cyclodextrin (β-CD)-functionalized reduced graphene (rGO)-modified GCE β-CD-rGO/GCE, the proposed CP5-rGO/GCE sensor exhibits excellent electrochemical catalytic activity, rapid response, high sensitivity, good reproducibility and anti-interference ability towards MP. The recognition mechanism of β-CD/MP and CP5/MP was studied by 1 H NMR. The results indicate a higher supramolecular recognition capability between CP5 and MP compared to that between β-CD and MP. The β-CD-rGO and CP5-rGO nano-composites were prepared via a wet chemistry approach. The resulting nano-composites have been characterized by thermogravimetric analysis (TGA), fourier transform infrared spectrometry (FTIR), charge transfer resistance ( R ct ) and zeta potential. The CP5-rGO/GCE combines the merits of CP5 and rGO, and is used for quantitative detection of MP. It has a low detection limit of 0.0003 μM (S/N = 3) and a linear response range of 0.001–150 μM for MP. This method has been used to detect MP in soil and waste water samples with satisfactory results. This study provides a promising electrochemical sensing platform and is a promising tool for the rapid, facile and sensitive analysis of MP.